2004
DOI: 10.1124/jpet.103.063107
|View full text |Cite
|
Sign up to set email alerts
|

Bremazocine Increases C-Type Natriuretic Peptide Levels in Aqueous Humor and Enhances Outflow Facility

Abstract: A relatively selective agonist of opioid receptors (KOR), bremazocine (BRE), lowers intraocular pressure in rabbits, in part, by increasing natriuretic peptide levels in aqueous humor and by enhancing total outflow facility (TOF). Natriuretic peptide (NP) levels [atrial NP (ANP), brain NP (BNP), and C-type NP (CNP)] were measured in aqueous humor of rabbits either by radioimmunoassay or enzyme immunoassay. TOF was determined in rabbits by two-level constant pressure perfusion of the anterior chamber. Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…If there is no dramatic developmental or structural abnormality in the angle, then the increase in C t must have been functional and have been triggered by the increase in F a . Others have proposed that the ciliary body communicates with the TM via the aqueous humor 2325. The mechanism underlying this putative communication is unknown although bioactive peptides have been suggested as one possible mechanism 2325.…”
Section: Discussionmentioning
confidence: 99%
“…If there is no dramatic developmental or structural abnormality in the angle, then the increase in C t must have been functional and have been triggered by the increase in F a . Others have proposed that the ciliary body communicates with the TM via the aqueous humor 2325. The mechanism underlying this putative communication is unknown although bioactive peptides have been suggested as one possible mechanism 2325.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm this evidence that the suppressive action of natriuretic peptides was mediated by NP receptors, we evaluated the effect of isatin, a nonselective natriuretic peptide receptor antagonist (Telegdy et al, 2000;Potter et al, 2004), on CNP-induced changes in TEER in ARPE-19 cells. In the presence of isatin (100 mM), pretreatment with CNP (10 nM) did not significantly alter the reduction in TEER induced by Glyc-alb.…”
Section: Resultsmentioning
confidence: 99%
“…Although several studies have used isatin as a selective NPR1 antagonist (Katoli et al, 2010), it has also been shown that at high enough concentration it can antagonize all three NP receptors (Telegdy et al, 2000;Potter et al, 2004;Katoli et al, 2010). Isatin is an indole molecule; nevertheless, it has little effect on the many neurotransmitter and hormonal receptors in the rat hippocampus, acting primarily as an inhibitor of atrial natriuretic peptide binding (Telegdy et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Topical application of a selective κ opioid agonist, bremazocine, has been shown to reduce aqueous humor flow rate presumably by increasing atrial natriuretic peptide levels [13], [14], [15]. A second selective κ agonist, spiradoline, was found to increase NO levels in both ciliary and trabecular meshwork cells, an action that would decrease aqueous humor production and increase its outflow [3].…”
Section: Discussionmentioning
confidence: 99%